Pharmacology Management in Improving Exercise Capacity of Patients with Fontan Circulation: A Systematic Review and Meta-analysis - Mendel, Brian; Christianto; Setiawan, Moira; Siagian, Sisca N.; Prakoso, Radityo (Current Cardiology Reviews, 2022)
Background: The Fontan procedure is currently the mainstay therapy for single functional ventricles. However, with prolonged follow-up duration, various complications have been observed that seriously influence the quality of life of patients. Objectives: The aim of this meta-analysis is to compare the effectiveness of pharmacologic agents in improving exercise capacity in patients with Fontan circulation. Methods: This meta-analysis was conducted according to the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) statement and has been registered in the International Prospective Register for Systematic Reviews database with registration no. 282352. Quality assessments of the included studies were assessed using the Strengthening Reporting of Observational Studies in Epidemiology (STROBE) statement. Results: Twelve studies met the predetermined inclusion criteria and were included in this metaanalysis. This meta-analysis found that treatment with bosentan significantly improved New York Heart Association Functional Class (NYHA FC) in Fontan patients (standard mean difference - 0.59, 95% CI -0.94 – -0.25; P=0.0008; I2 = 1%). However, the use of bosentan (P=0.66) and sildenafil (P=0.13) did not show a significant improvement in the maximum rate of oxygen consumption (VO2 max). Conclusion: This meta-analysis shows that people with Fontan circulation may benefit from using bosentan as it decreases postexercise heart rate and improves NYHA FC and 6-minute walking test results. Therefore, indirectly improving exercise capacity. Nonetheless, considerable work is required to strengthen our knowledge in improving the exercise capacity of Fontan patients.
Keywords: vasodilator